Substrate dependent talitrid amphipods from fragmented beaches on the north coast of Crete (Crustacea, Amphipoda, Talitridae), including a redefinition of the genus Orchestia and descriptions of Orchestia xylino sp. nov. and Cryptorchestia gen. nov. - Lowry, J. K.; Fanini, Lucia (Zootaxa, 2013)
Four species of talitrid amphipods (Orchestia montagui Audouin, 1826, Orchestia stephenseni Cecchini, 1928, Orchestia xylino sp. nov. and Talitrus saltator (Montagu, 1808)) are reported from a set of fragmented pocket beaches to the east of Heraklion on the north coast of Crete. Aside from a previous record of O. stephenseni these are the first records of talitrid amphipods from the island of Crete. 2) Along a coastal segment of only 4.36 km, characterised by habitat fragmentation and substrate patchiness, a clear correlation between talitrid species and beach type is indicated. Talitrus saltator occurs only on sandy beaches. Orchestia montagui and O. xylino occur on banquette beaches and O. montagui, O. stephenseni and O. xylino occur on mixed sand/gravel and cobble beaches. 3) The genus Orchestia is redefined and confined to 15 marine supralittoral species from eastern North America, islands in the North-eastern Atlantic, and western-Europe, including the Baltic and the Mediterranean Seas plus a perplexing group in New Zealand. 4) The new genus Cryptorchestia is described, based on nine terrestrial species previously included in the genus Orchestia and occurring in western Europe, the Mediterranean Sea and the Azores and Canary islands in the North-eastern Atlantic. 5) The new species Orchestia xylino sp. nov. is described. 6) An extensive bibliography for the species in this study is provided.